2008
DOI: 10.1016/j.biortech.2008.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation as the anaerobic pre-treatment of fats: Oleate conversion using RuO2 and IrO2 based anodes

Abstract: Electrochemical treatment of oleate using RuO2 and IrO2 type dimensionally stable anodes in alkaline medium was performed to develop a feasible anaerobic pre-treatment of fatty effluents. The results showed that the pre-treated solutions over RuO2 were faster degraded by anaerobic consortium than the raw oleate solutions or the electrolysed solutions using IrO2. In batch experiments carried out with pre-treated solutions over RuO2 (100-500mg/L), no lag phases were observed before the methane production onset. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Various types of electrodes such as graphite [16], activated carbon fibre [17], Pt [18][19][20][21] and boron doped diamond electrodes (BDD) [22][23][24][25] have been studied but, in the last years, Dimensionally Stable Anodes (DSA) have arisen great interest as one of the promising electrodes. Currently, their use for the degradation of organic pollutants is an active area of research [26][27][28][29]. In this sense, anodes coated with SnO 2 exhibit high overpotential for oxygen (Á O 2 ) and chlorine evolution [30,31], good stability, low resistivity and high electrical conductivity (thanks to doping).…”
Section: Introductionmentioning
confidence: 99%
“…Various types of electrodes such as graphite [16], activated carbon fibre [17], Pt [18][19][20][21] and boron doped diamond electrodes (BDD) [22][23][24][25] have been studied but, in the last years, Dimensionally Stable Anodes (DSA) have arisen great interest as one of the promising electrodes. Currently, their use for the degradation of organic pollutants is an active area of research [26][27][28][29]. In this sense, anodes coated with SnO 2 exhibit high overpotential for oxygen (Á O 2 ) and chlorine evolution [30,31], good stability, low resistivity and high electrical conductivity (thanks to doping).…”
Section: Introductionmentioning
confidence: 99%
“…They found that acidogenesis increased 166.7%, VFA ratios increased 732%, and VS decreased 17.0%. In another pre-treatment evaluation, oleate electro-oxidation preceded anaerobic treatment (Goncalves et al, 2008). The researchers found improved oleate conversion to methane and reduced lag periods when a rubidium oxide electrode was applied versus an iridium oxide electrode or no pre-treatment.…”
Section: Maciasmentioning
confidence: 99%
“…Although pesticides have been detected in water since the 1950's, in the last 15 years their use has risen dramatically all over the world and has nearly doubled every 5 years since 1975. On this way, chloro phenols(CPs) constitute a particular group of priority toxic pollutant listed by USEPA (environmental protection agency) in the clean water act [2][3][4][5][6][7] and by the European decision 2455/2001/EC [1,[8][9][10][11][12], because most of them are toxic and hardly biodegradable and difficult to remove from environment. Various contaminations such as azo dyes, organo chlorine and dramatic hydrocarbons have been ducted, and a number of the chemical components are suspected of being endocrine disrupting chemicals (EDCs).…”
Section: Introductionmentioning
confidence: 99%